2023
DOI: 10.1111/1471-0307.12955
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of the methods of administering lactoferrin, IGF‐1 and IgG from bovine colostrum to rabbits based on the cytokine communication network

Abstract: Lactoferrin, IGF‐1 and IgG are three well‐known bioactive proteins found in bovine colostrum. We studied the effects of these three active ingredients on the levels of eight cytokines in serum and on the cellular communication networks in vivo by oral administration, intraperitoneal injection and intravenous injection. The results suggested that bioactive ingredients, especially biomacromolecules, can induce different effects, even opposite effects, on the immune system depending on the route of administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…47 Several clinical studies have suggested that the mechanism by which bovine colostrum exerts an immune function might result from its anti-inflammatory effects on various intestinal inflammatory diseases. 22,48,49 Previously, Lu and colleagues investigated the effect of IgG on serum cytokines levels through different administration methods, and the results showed that oral administration with IgG exhibited a pro-inflammatory function in rabbits, as manifested by upregulation of the pro-inflammatory cytokines levels ( e.g. , TNF-α, IFN-γ, and IL-1β) and downregulation of the anti-inflammatory cytokines levels ( e.g.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…47 Several clinical studies have suggested that the mechanism by which bovine colostrum exerts an immune function might result from its anti-inflammatory effects on various intestinal inflammatory diseases. 22,48,49 Previously, Lu and colleagues investigated the effect of IgG on serum cytokines levels through different administration methods, and the results showed that oral administration with IgG exhibited a pro-inflammatory function in rabbits, as manifested by upregulation of the pro-inflammatory cytokines levels ( e.g. , TNF-α, IFN-γ, and IL-1β) and downregulation of the anti-inflammatory cytokines levels ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…, IL-4 and IL-10), while the intraperitoneal and intravenous injection of IgG showed anti-inflammatory activities. 22 Besides, transcriptomic studies conducted by Asbjornsdottir et al suggested that the bioactive components in bovine colostrum, such as IgG and lactoferrin, might exert anti-inflammatory properties by regulating the NF-κB signaling pathway. 4 Our current research indicated that CTX caused an imbalance between the immunity-related cytokines and destroyed the intestine structure in BALB/c mice, and interestingly, after encapsulating by liposomes, bovine colostrum showed better characteristics for enhancing the IgG levels, rehabilitating the anti-inflammatory cytokines levels, and improving the intestine structure (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations